Modeling of Jakarta Islamic Index Stock Volatility Return Pattern with Garch Model - Faizul Mubarok; Muhammad Faturrahman Aria Bisma (Al-Tijary, 2020)
Along with the large number of investors transacting on Islamic stocks, the movement of stock prices becomes more volatile. The purpose of this research is to examine the behavior of volatility patterns in shares incorporated in the Jakarta Islamic Index using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model. This study uses daily data from six stocks contained in the Jakarta Islamic Index during the period January 1, 2009, to December 31, 2019. Data volatility is seen using the GARCH model. Estimation results for daily data show that the volatility of ASII, SMGR, TLKM, UNTR, and UNVR shares is influenced by the error and return volatility of the previous day. This is indicated by the GARCH effect on each regression result. The results of the study are beneficial for an investor, and if you want to invest with a low level of risk, you can choose TLKM shares. But if you're going to get a high level of return, you can invest in UNTR shares. For securities analysis, you can use the GARCH model that has been tested to predict volatility in the Jakarta Islamic Index.